Konsep Pendidikan Karakter dalam Pemikiran Thomas Lickona “Strategi Pembentukan Karakter yang Baik” - Susanti, Salamah Eka (Lembaga Yasin AlSys, 2022)
The study of this paper focuses on the study of the thought figure of Thomas Lickona. Thomas Lickona is a researcher and educational activist who lives in America, especially character education. Thomas Lickona in his view of character education has a theory of character education, he says that there are three things that are at the core of character education, namely, nowing the good (good knowledge), viling the good (love of goodness), action the good (deeds the good one). This study aims to determine Thomas Lickona's character education concept as a strategy for building good character for students. This research method uses library research. This research is descriptive analytic in nature, namely explaining and analyzing Thomas Lickona's thoughts about character education in a systematic way so that it is easy to understand. The results of this study are, when researched and analyzed, basically Thomas Lickona's thoughts or character education theory quotes a lot or is inspired by the thoughts of Ancient Greek philosophy and Islamic philosophy, especially the thoughts of Ibn Miskawaih in the Book of Tahdibul Akhlak, where he says that there are ten The main ethics or morals that must be instilled in students are: wisdom, justice, patience, self-control, love, positive attitude, hard work, sincerity, gratitude or gratitude, and humility.